Analysis : From Operational Frameworks to Classical-Keynesian Theoretical Debates - Muhammad Permadi; Atin Risnawati (Politeknik Siber Cerdika Internasional, 2026)
Macroeconomic monetary policy is a key instrument in maintaining economic stability through the control of inflation, interest rates, and money supply. In the theoretical framework, the ideas of John Maynard Keynes emphasize the importance of an active role of monetary authorities in stimulating the economy, particularly during periods of declining aggregate demand. This Keynesian approach is reflected in expansionary monetary policies such as lowering interest rates and increasing liquidity to encourage investment and consumption. In international practice, countries such as the United States through the Federal Reserve and Japan through the Bank of Japan have implemented similar policies, especially during global economic crises, by using both conventional and unconventional instruments such as quantitative easing. However, modern monetary policy is not purely Keynesian, as it combines various approaches to maintain macroeconomic stability. Therefore, macro monetary policy across countries is adaptive and contextual, aiming to ensure financial system stability, support economic growth, and improve public welfare.